What about livestock? Here’s how Kenya and ILRI are building climate resilience in the Sector - International Livestock Research Institute (Nation Media Group, 2022)
Kenya is a leader in climate-change research and policy in Africa. ILRI takes great pride in partnering with Kenya on work that is improving the livelihoods of its smallholder farmers and herders, as well as food and nutritional security for the whole population.